(untitled) (Architecture Image Studies, 2025)
This study aims to 1) study the historical background of talismans in the Lower Northeast, 2) study the forms of talismans in the Lower Isaan Region, and 3) study the processes of creating new meanings for talismans in the Lower Isaan Region. The population and sample for this study are the Lower Isaan Region. Data collection tools included a survey, observation form, and interview form. The study employed the concept of mythology and the integration of beliefs, folklore theory, cultural diffusion theory, aesthetics theory, and semiotics theory as analytical frameworks. From the study, talismans in the Lower Isaan Region can be classified into two types: natural talismans, such as elephant tusks, python fangs, Lek Lai, Kod, and boar tusks; and human-made talismans, such as Takrud, beeswax, exorcist’s knives, Nang Gwok, and Bia Kae. These beliefs are fundamentally rooted in faith in supernatural powers, which have been deeply embedded in the way of life since ancient times, linked to Animism, Hinduism, and Buddhism. Currently, these beliefs continue to strongly influence the way of life in the Lower Isaan Region, adapting to modern times. New meanings are created through storytelling, media promotion, rituals, interpretation by outsiders, and economic exchange, integrating various forms of beliefs in terms of shapes, materials, creation processes, and functions. The changes and creation of new meanings reflect efforts to adapt to contemporary demands. Nevertheless, preserving the original meanings of these talismans remains crucial to ensure the continuation of this valuable cultural heritage.